Partner selection and the division of surplus: Evidence from ultimatum and dictator experiments - Priyodorshi Banerjee; Sujoy Chakravarty; Sanmitra Ghosh (Games, 2016)
We study ultimatum and dictator environments with one-way, unenforceable pre-play communication from the proposer to the recipient, semantically framed as a promise. After observing this promise regarding how much the proposer will offer if selected, in our treatment conditions, recipients choose whether or not to select a particular proposer. We find that offers can increase in the ultimatum game both with non-competitive selection with a single potential proposer, and more so with competition, where the recipient chooses one of two potential proposers, as compared to the no selection baseline. Furthermore, the offer is rejected with higher probability if the promisemade by the selected proposer is higher than the eventual offer. Our dictator environment does not give the power to reject offers, thus selection power carries no benefits in the dictator game. Finally, independent of the game institution or proposer selection mechanism, promises provide credible signals for offers.
Keywords: C78; C91; D03; 330; dictator and ultimatum games; non-binding communication with intent; partner selection; competing promises; credibility and credulity